Effects of CO2 on sulfur removal and its release behavior during coal pyrolysis. (1st February 2016) - Wang, Xinlong; Guo, Huiqing; Liu, Fenrong; Hu, Ruisheng; Wang, Meijun
Abstract: In this study, two Chinese coals, Jiexiu (JX) and Yanzhou (YZ) raw coals, their deashed coals and depyrited coals, were used to investigate the effects of CO2 on sulfur removal and its release behavior during coal pyrolysis by pyrolysis with mass spectrometer (Py-MS) and pyrolysis connected with gas chromatogram (Py-GC). It is found that the sulfur removal ratio of YZ and JX coals under CO2 atmosphere is higher than that under Ar atmosphere. Most sulfur removal of JX coal is distributed in tar under Ar atmosphere, while it is distributed in gas phase under CO2 atmosphere. The CO2 atmosphere is very beneficial to H2 S, COS and SO2 release into gas phase. That is the maximum evolution peak temperature of H2 S and SO2 decreases, and their evolution amount all increase remarkably, especially for COS evolution. The COS evolution of each coal increases with temperature increasing after 850 °C under CO2 atmosphere. This further validates COS formation is related to CO at higher temperatures, while it is unrelated to CO at lower temperatures.